PENGARUH PELAKSANAAN PEMBELAJARAN CNC BERBASIS CAI TERHADAP PENINGKATAN TARAF BERFIKIR INTERAKTIF SISWA PADA MATERI MENGOPERASIKAN MESIN CNC DASAR DI SMK - Robby Cahaydi, Wahyu; Susila, I Wayan; Endah Palupi, Aisyah (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract Strategic use of media as a companion in the learning process is needed to address the problems that arise in the learning process, one of which is a computer-based learning model. The learning system is packaged in the form of software (software) computer is an enhancement rather than the unified information communication technology (interactive), audio, video, image appearance (image) is called multimedia technology. Computer Assisted Instruction (CAI) include the use of a computer that is directly related to students and educators, allowing each student to learn individually, independently (mastery learning) in accordance with the speed and capabilities of each. This study aims to determine the extent to which the implementation of the application of Computer-based learning media Asissted Instruction (CAI) in the form of tutorials in subjects CNC line with current technological developments, as well as prepare students to enter the workforce and develop a professional attitude. Another goal is to find the influence of interactive thinking ability of students to the learning outcomes are emphasized in the simulation. This research method using descriptive analysis with a quantitative approach. The population is all students of class XII SMK Antarctic TPM 1 Sidoarjo. Sample was determined by random cluster sampling consisted of 59 students. The data was collected using the technique of testing. Analysis using linear regression and descriptive. Results of the execution of the application of CAI-based instructional media in learning can be used well in lessons operate CNC machine base with an average value of 3.48, interactive thinking skills to think quite active with the average value of 3.20 and the learning outcomes of the performance assessment tests to test results learning increased with an average value that is; 80. The correlation coefficient of R = 0.289 are included in the significant criteria. Regarding the influence of interactive thinking ability of students to student learning outcomes in the implementation of the CAI instructional media implementation is shown by the coefficient of determination of R2 = 0.083 or 10%, which means that the student learning outcomes can be influenced by interactive thinking skills of students as a percentage of 10% while 90% be affected by other factors. From the results of tests of significance, showed that the effect is significant at the significant level ? = 0.05 with the Sig learning outcomes. (2-tailed) of 0.027 (0.027 ? 0.05), then Ho is rejected and Ha accepted significant meaning. It is evident that interactive thinking ability of students has a significant relationship to the learning outcomes. Keywords: Improved Learning Outcomes, Learning Media CAI. PENDAHULUAN Belajar adalah suatu proses yang kompleks yang terjadi pada diri setiap orang sepanjang hidupnya. Proses belajar itu terjadi karena adanya interaksi antara seseorang dengan lingkungannya. Salah satu pertanda bahwa seseorang itu telah belajar adalah adanya perubahan tingkah laku pada diri orang itu yang mungkin disebabkan oleh terjadinya perubahan pada tingkat pengetahuan (kognitif), ketrampilan (psikomotor), atau sikapnya (afektif). Apabila proses belajar itu diselenggarakan secara